Characterization of Unexplored Deadwood Mycobiome in Highly Diverse Subtropical Forests Using Culture-independent Molecular Technique - Purahong, Witoon; Pietsch, Katherina A.; Lentendu, Guillaume; Schöps, Ricardo; Bruelheide, Helge; Wirth, Christian; Buscot, François; Wubet, Tesfaye (Frontiers in Microbiology, 2017)
The deadwood mycobiome, also known as wood-inhabiting fungi (WIF), are among the key players in wood decomposition, having a large impact on nutrient cycling in forest soils. However, our knowledge of WIF richness and distribution patterns in different forest biomes is limited. Here, we used pyrotag sequencing of the fungal internal transcribed spacer (ITS2) region to characterize the deadwood mycobiome of two tree species with greatly different wood characteristics (Schima superba and Pinus massoniana) in a Chinese subtropical forest ecosystem. Specifically, we tested (i) the effects of tree species and wood quality properties on WIF OTU richness and community composition; (ii) the role of biotic and abiotic factors in shaping the WIF communities; and (iii) the relationship between WIF OTU richness, community composition and decomposition rates. Due to different wood chemical properties, we hypothesized that the WIF communities derived from the two tree species would be correlated differently with biotic and abiotic factors. Our results show that deadwood in subtropical forests harbors diverse fungal communities comprising six ecological functional groups. We found interesting colonization patterns for this subtropical biome, where Resinicium spp. were highly detected in both broadleaved and coniferous deadwood. In addition, the members of Xylariales were frequently found in Schima. The two deadwood species differed significantly in WIF OTU richness (Pinus > Schima) and community composition (P < 0.001). Variations in WIF community composition of both tree species were significantly explained by wood pH and ecological factors (biotic: deadwood species, basal area and abiotic: soil pH), but the WIF communities derived from each tree species correlated differently with abiotic factors. Interestingly, we found that deadwood decomposition rate significantly correlated with WIF communities and negatively correlated with WIF OTU richness. We conclude that the pattern of WIF OTU richness and community composition are controlled by multiple interacting biotic and abiotic factors. Overall, our study provides an in-depth picture of the deadwood mycobiome in this subtropical forest. Furthermore, by comparing our results to results from temperate and boreal forests we contribute to a better understanding of patterns of WIF communities across different biomes and geographic locations.